Interindividual spacing affects the finder's share in ring-tailed coatis (Nasua nasua). (23rd October 2019) - Hirsch, Ben T; Malpass, Erica; Di Blanco, Yamil E
Abstract: Social foraging models are often used to explain how group size can affect an individual's food intake rate and foraging strategies. The proportion of food eaten before the arrival of conspecifics, the finder's share, is hypothesized to play a major role in shaping group geometry, foraging strategy, and feeding competition. The variables that affect the finder's share in ring-tailed coatis were tested using a series of food trials. The number of grapes in the food trials had a strong negative effect on the finder's share and the probability that the finder was joined. The effect of group size on the finder's share and foraging success was not straightforward and was mediated by sociospatial factors. The finder's share increased when the time to arrival of the next individual was longer, the group was more spread out, and the finder was in the back of the group. Similarly, the total amount of food eaten at a trial was higher when more grapes were placed, arrival time was longer, and the number of joiners was smaller. Individuals at the front edge of the group found far more food trials, but foraging success was higher at the back of the group where there were fewer conspecifics to join them. This study highlights the importance of social spacing strategies and group geometry on animal foraging tactics and the costs and benefits of sociality. Lay Summary: Coatis, a group living mammal, search for food and feed together. Individuals at the front of the group and far from other group members consume more food than other group members. The spacing of individuals in a group can be more important than the number of group members in determining feeding success. This strategy of searching for food away from others is a strategy for animals to reduce competition for food and acquire more resources.